1964
DOI: 10.1037/h0045689
|View full text |Cite
|
Sign up to set email alerts
|

Information capacity of discrete motor responses.

Abstract: The effects of response amplitude and terminal accuracy on 2-choice reaction time (RT) and on movement time (MT) were studied. Both the required amplitude (A) of a movement, and the width (W) of the target that S was required to hit, had a large and systematic effect on MT, whereas they had a relatively small effect on RT. Defining an index of movement difficulty as ID = log^B2)2A/W, the correlation between ID and MT was found to be above .99 over the ID range from 2.6 to 7.6 bits per response. Thus the times … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
677
9
15

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,311 publications
(743 citation statements)
references
References 16 publications
42
677
9
15
Order By: Relevance
“…5; hitting back later corresponds to negative values, where the vertical extent of the shaded area is smaller). The optimal speed for intercepting a target is one that finds the right balance (Brouwer et al 2000) between moving slowly to improve the spatial resolution (Fitts and Peterson 1964) and moving fast to improve the temporal resolution (Schmidt 1969). The fact that the disk had to pass through the goal probably forced our subjects to move faster than would be optimal for hitting a chosen spot on the target's edge.…”
Section: The Strategymentioning
confidence: 99%
“…5; hitting back later corresponds to negative values, where the vertical extent of the shaded area is smaller). The optimal speed for intercepting a target is one that finds the right balance (Brouwer et al 2000) between moving slowly to improve the spatial resolution (Fitts and Peterson 1964) and moving fast to improve the temporal resolution (Schmidt 1969). The fact that the disk had to pass through the goal probably forced our subjects to move faster than would be optimal for hitting a chosen spot on the target's edge.…”
Section: The Strategymentioning
confidence: 99%
“…The relationship between these two variables has been formalized as Fitts' law. 23,24 It states that movement time (MT) is a linear function of the index of difficulty (ID ¼ Log2 [2A/W]), where A is the amplitude of the movement and W the width of the target (accuracy constraint).…”
Section: Introductionmentioning
confidence: 99%
“…There have been some previous attempts to address this issue. In his original study, Fitts reported the reaction times in addition to the movement times recorded in a repetitive tapping task (Fitts 1954;Fitts & Peterson 1964). The results suggested that RT was influenced by the task constraints but the relationship was weak.…”
Section: Introductionmentioning
confidence: 99%